ANALISIS KINERJA KARYAWAN DIVISI SALES PADA PT PUTRA BORNEO NUSANTARA INDAH - Fitra Aprilindo Sase; Mayang Nurwulan Sari; Yulius Jatmiko Nuryatno (ITB AAS Indonesia Surakarta, 2023)
This study aims to analyze the effect of work ethic and job training variables on employee performance in the sales division at PT Putra Borneo Nusantara Indah. During 2021, monthly vehicle retail sales were only able to reach the target in June. This is thought to be influenced by the work ethic and job training variables. The method used in this research is multiple linear regression analysis. Respondents in this study were 29 employees of the sales division of PT Putra Borneo Nusantara Indah. The research instrument used was a questionnaire with a Likert scale of 1-6. Testing the feasibility of the instrument found valid and reliable results. The results showed that the influence of work ethic and job training variables on employee performance compared to other variables not examined was 75.3%. The results of hypothesis testing indicate that there is a significant effect both partially and simultaneously on the work ethic and job training variables on employee performance.